Aligned-SWCNT film laminated nanocomposites: Role of the film on mechanical and electrical properties. (November 2018) - Sui, Chao; Pan, Zixuan; Headrick, Robert J.; Yang, Yingchao; Wang, Chao; Yuan, Jiangtan; He, Xiaodong; Pasquali, Matteo; Lou, Jun
Abstract: In this study, well-aligned single-walled carbon nanotube (SWCNT) films were utilized as lamellae to prepare a multifunctional nanocomposite by a feasible 'layer-by-layer' preparation method. This structural design can not only dramatically reduce the agglomeration effect of SWCNTs, but also achieve high in-plane stiffness. It was found that the well-aligned SWCNT films contribute to the high stress-transfer between CNTs and present good wettability with epoxy matrix, thereby improving the mechanical enhancement. Interestingly, this laminated structure possesses distinct electrical behaviors under different loading conditions. The electrical resistance linearly increases with the increase of in-plane tensile strain but is insensitive to bending. This work could provide in-depth understanding on the mechanical and electrical properties of CNT-based laminated nanocomposites. Graphical abstract: Image 1